2008
DOI: 10.1177/00238309080510010701
|View full text |Cite
|
Sign up to set email alerts
|

Scope-marking Strategies in the Acquisition of Long Distance wh-Questions in French and Dutch

Abstract: This paper reports the results of an elicited production task of Long Distance (LD) wh-questions conducted with typically developing French- and Dutch-speaking children aged four and six, and adult control groups for each language. It is shown that besides input-convergent wh-questions, in both languages children use nontarget strategies to express scope. While in both French and Dutch children produce Partial Movement and wh-copying questions, only French children use Partial Movement without an overt scope-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 26 publications
7
60
0
2
Order By: Relevance
“…Fanselow, 2006;Müller, 1997;Van Kampen, 1997). This observation seems to be corroborated by a recent elicitation study by Jakubowicz & Strik (2008), where Dutch adult subjects predominantly produced standard LD wh-movement constructions, contrary to Dutch children, who produced a considerable amount of partial wh-movement and wh-copy constructions. The absence of partial whmovement and wh-copying in Dutch is however surprising, since these constructions do show up in closely related languages including German, (McDaniel, 1989), Frisian (Hiemstra, 1986) and Afrikaans (Du Plessis, 1977), and also in a large number of Dutch dialects (cf.…”
Section: Partial Wh-movement and Wh-copying In Dutchsupporting
confidence: 71%
“…Fanselow, 2006;Müller, 1997;Van Kampen, 1997). This observation seems to be corroborated by a recent elicitation study by Jakubowicz & Strik (2008), where Dutch adult subjects predominantly produced standard LD wh-movement constructions, contrary to Dutch children, who produced a considerable amount of partial wh-movement and wh-copy constructions. The absence of partial whmovement and wh-copying in Dutch is however surprising, since these constructions do show up in closely related languages including German, (McDaniel, 1989), Frisian (Hiemstra, 1986) and Afrikaans (Du Plessis, 1977), and also in a large number of Dutch dialects (cf.…”
Section: Partial Wh-movement and Wh-copying In Dutchsupporting
confidence: 71%
“…Medial wh-constructions were first attested in child L1 English by see also McDaniel et al, 1995) and included wh-copying, as in (2), and wh-scope marking, as in (3). 2 Similar constructions were subsequently attested in the L1 acquisition of other languages, including Dutch (Jakubowicz and Strik, 2008;van Kampen, 1997), French (Jakubowicz and Strik, 2008;Oiry and Demirdache, 2006), Spanish (Gutierrez, 2004a), and Basque (Gutierrez, 2004b). 3 Furthermore, studies have shown that such constructions may also exist in the L2 English of speakers whose L1s include Japanese (Schulz, 2006;Wakabayashi and Okawara, 2003;Yamane, 2003), German (Schulz, 2006), and bilingual Spanish/Basque (Gutierrez, 2005).…”
Section: Introductionmentioning
confidence: 72%
“…Apart from these general goals, the specific purpose of this article is to apply the derivational complexity hypothesis, henceforth DCH (Jakubowicz, 2004(Jakubowicz, , 2005(Jakubowicz, , 2011Jakubowicz and Strik, 2008;Strik and Pérez-Leroux, 2011) to L2 data. While this hypothesis has so far been used mostly in L1 acquisition, I show that it has strong potential in adult L2 acquisition (for a study testing this hypothesis in child L2, see also Prévost et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ora, se assumirmos uma métrica de complexidade em que cada nova operação (de movimento) aumenta o nível de complexidade da estrutura (cf. Jakubowicz, 2004Jakubowicz, , 2005Jakubowicz, , 2011Jakubowicz & Strik, 2008), esperaríamos resultados Revista da Associação Portuguesa de Linguística inversos aos encontrados nas crianças, i.e., esperaríamos percentagens de acerto superiores na compreensão de estruturas de topicalização do que nas de sujeitos periféricos à direita, já que nestas há mais um movimento do que naquelas.…”
Section: Revista Da Associação Portuguesa De Linguísticaunclassified